Konstruksi Idiologi Dalam Tradisi Mabuug-buugan di Desa Adat Kedonganan, Kuta, Bali - sudarsana; Wiresna , Asep Ganjar (Paraguna, 2025)
This study aims to analyze and reveal the ideological construction in the Mabuug-Buugan tradition in the traditional village of Kedonganan, Kuta, Bali. The Mabuug-Buugan tradition is an annual ritual held the day after Nyepi Day as a symbol of purification of oneself and the environment from negative energy. This study uses a qualitative approach with ethnographic methods to explore the values, beliefs, and symbolism contained in the ritual. Data was obtained through observation, in-depth interviews with traditional leaders, and analysis of relevant documents and literature. The results of the study indicate that the ideological construction within the Mabuug-Buugan tradition encompasses several key aspects: (1) a religious ideology emphasizing harmonious relationships between humans, nature, and God through the teachings of Tri Hita Karana; (2) sacred and spiritual values manifested through the use of mud as a symbol of self-purification; (3) an ideology of preserving local culture amid the growing tide of modernization; and (4) collective identity and community solidarity that strengthen social bonds among village residents. This tradition also reflects resistance to consumerism, which conflicts with local cultural principles. Thus, the Mabuug-Buugan tradition has become an important means for the people of Kedonganan Village to preserve their identity, values, and local wisdom inherited from their ancestors. The results of this study are expected to contribute to cultural studies and serve as a reference for the development of cultural preservation policies in Bali.